How to Begin to Overcome the Ambiguity Present in Differentiation between Contents and Levels of Consciousness? - Bachmann, Talis (Frontiers in Psychology, 2012)
Recently, a welcome trend has emerged – in addition to the traditional studies on contents and states of consciousness, levels of consciousness have become a matter of research. However, there are some conceptual and methodological difficulties with this research – the labels used for empirical measurement of levels are ambiguous and underspecified while the research on neural correlates of consciousness has not been well linked to psychophysical approaches to studying the levels of consciousness. This article suggests a perspective on how to advance the psychophysics of measuring the levels by precisely specifying level-specific contents and how to relate the distinction between contents and levels to the distinction between the underlying brain mechanisms necessary for processing contents and regulating the level of consciousness.